An Email to my teacher : Digital literacy activities for building students’ self-confidence: Digital literacy activities for building students’ self-confidence - Mardiah, Radiatan; Melati, Melati (International Journal of English Language and Pedagogy, 2025)
Digital literacy skills help students to make the most of the opportunities and face the challenges that digital technologies and online environments provide. However, some students find the digital literacy skills, particularly writing and receiving emails challenging because of their lack of confidence and experience. This study describes learning activities providing students with the opportunity to engage with the academic community to promote email communication and raise their self-confidence. The participants of this qualitative study were non-English education department students who enrolled in English course in a public university in Jambi, Indonesia. The data were the students’ email collected through the use of university learning management system and their reflection collected through classroom discussion. Learning activities which involve students in real experience of writing and receiving email communication were applied. Interpreted qualitatively, the data show that all participants are able to write an email in English to their self-selected teacher in their academic community and received the response from the teacher. The result indicates that the activities enhance the students’ confidence in writing English email although there are still some mistakes in the technical part of their writing. Real world practice of the digital literacy skills is strongly suggested.